Exploring the Lived Experiences of Instrumental Ensemble Performers With Dalcroze Eurhythmics: An Interpretative Phenomenological Analysis - Wentink, Catrien; Van der Merwe, Liesl (Frontiers in Psychology, 2020)
The purpose of this interpretative phenomenological analysis (IPA) is to explore the way that instrumental ensemble performers understand their experiences of Dalcroze Eurhythmics while preparing the Tango and Charleston of the jazz ballet, La revue de Cuisine, by Bohuslav Martinů. The participants of this study were the members of an ad hoc ensemble, which included both authors. Data included semi-structured interviews and reflections by the first author during and after the five Dalcroze sessions. The six emergent super-ordinate themes were: 1. Heightened awareness of music, time, space and energy; 2. Beneficial for relationships in the ensemble; 3. Improved musicianship; 4. Enjoyment and feeling good; 5. Informing pedagogy; and 6. Social and cognitive challenges. Implications of this study suggest that Dalcroze experiences link with Csikszentmihalyi’s description of the experience of ‘flow’. Experiences of flow are very positive emotions, which will be beneficial for the performers in any instrumental ensemble.